Getting it Right from the Start (GIRFTS): protocol for a stepped-wedge cluster randomised controlled trial of a school-based framework to improve children's oral language and reading outcomes - Jon Quach; Sharon Goldfeld; Lisa Gold; Patricia Eadie; Francesca Orsini; Pamela Snow; Beth Shingles; Judy Connell; Melissa L Siew; Cecilia Sinclair; Shiralee Poed; Stuart Edwards (BMJ Publishing Group, 2024)
Introduction Strong oral language and reading skills are important for child development. The response to intervention (RTI) framework supports schools to apply evidence-based practices and interventions to proactively meet the learning needs of all students and identify and support students at risk of learning difficulties. Getting it Right from the Start (GIRFTS) aims to implement a codesigned RTI framework in the first 2 years of formal schooling (foundation and grade 1) to improve oral language and reading skills. GIRFTS includes an implementation evaluation.Methods and analysis GIRFTS is a stepped-wedge cluster randomised trial conducted in Victoria, Australia, over 3 years. Clusters are primary schools. The intervention is to implement tiers 1 and 2 of the RTI framework into foundation and grade 1 according to RTI principles. The primary outcome is reading comprehension by the start of grade 2. Secondary outcomes include listening comprehension, word and non-word reading and phonological awareness. An implementation evaluation will also be conducted with the study to understand schools' RTI implementation process and enablers and barriers to implementation. Strategies used by schools to overcome implementation challenges will also be investigated.Ethics and dissemination This trial was approved by the Royal Children's Hospital Human Research Ethics Committee (HREC/58832/RCHM-2019). Investigators will communicate the results to stakeholders, collaborators and participating schools and teachers through presentations and publications.Trial registration numbers ISRCTN91164066, ACTRN12622000146796.